Brought Up to Be American: The Assimilation Process of Children and Teenage Refugees from Germany in the 1930s and 1940s in New York - Geneviève Susemihl (Current Objectives of Postgraduate American Studies)
The paper discusses the immigration and assimilation experiences of German refugees to New York in the 1930s and 40s, specifically the experiences of children and teenagers. It illustrates their integration process, focussing on various aspects of assimilation such as language, friendships, social life and school, investigates into consequences and effects of Americanization and examines the immigrants’ own evaluation of adjustment.